Global Perspectives on Amateur Film Histories and Cultures - Salazkina, Masha (Book collections on Project MUSE., 2021)
Together, these essays shed new light on alternative cinema in a wide range of cities and countries where amateur films thrive in the shadow of commercial and conventional film industries.